Pandangan Al-Qur’an Terhadap Persepsi Istilah Hari Sial Masyarakat Desa. Mojorejo Kec. Pungging Kab. Mojokerto - Mokhammad Saifuddin Azzuhri; Amir Mahmud; Wiwin Ainis Rohtih; Nyoko Adi Kuswoyo (4, 2024)
This study explores the beliefs of the people of Mojorejo Village, Pungging District, Mojokerto Regency towards the concept of